Overoxidized electropolymerized poly(pyrrole-1-propionic acid) on screen-printed graphene electrode-based electrochemical sensor for selective detection of dopamine neurotransmitters in the presence of norepinephrine and serotonin - Jeerakit Thangphatthanarungruang; Wichayaporn Kamsong; Chanchai Charonpongsuntorn; Papan Thaipisuttikul; Pisist Kumnorkaew; Patcharin Chaisuwan; Chanpen Karuwan (Electrochemistry Communications)
The accuracy and reliability of quantitative analysis are critical for the practical application of analytical methods. Hence, this study pioneered the use of overoxidized electropolymerized poly(pyrrole-1-propionic acid) on a screen-printed graphene electrode as an electrochemical sensor for the selective detection of dopamine (DOP) in the presence of norepinephrine (NOR) and serotonin (SER) at physiological levels in urine. These compounds are the primary monoamine neurotransmitters in the brain that are associated with specific symptoms of depression. The developed sensor was fabricated through a facile electropolymerization and overoxidation process of the polymer on the printed electrode via cyclic voltammetry. Previous results of important studies on electrode fabrication and characterization were verified through a field-emission scanning electron microscopy, energy dispersive X-ray spectroscopy, X-ray photoelectron spectroscopy, and electrochemical impedance spectroscopy. Under optimal conditions, the proposed sensor exhibited a dynamic concentration range of 250–5000 nM and a low detection limit of 16.53 nM for DOP detection. Moreover, the proposed method demonstrated highly selective DOP detection without interference from NOR and SER. To evaluate its biological applicability, we tested the developed method in synthetic urine samples. The proposed sensor can be productively used as an alternative electrochemical sensor with high accuracy and good precision. Therefore, this sensor is well-suited for quantitative analytical applications in the monitoring of DOP neurotransmitter levels in the nervous system, which can affect human health.